2002
DOI: 10.1345/aph.1a262
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sensitivity between Paroxetine and Sertraline

Abstract: The possibility of cross-reactivity between SSRI antidepressants should be considered by clinicians who wish to switch from one SSRI to another due to a dermatologic reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Cross‐sensitivity among different SSRIs has been suggested as some reports have described cutaneous eruptions experienced by the same patients to two or more of these drugs (5). It may be related to a shared mechanism of action or to a common excipient.…”
Section: Discussionmentioning
confidence: 99%
“…Cross‐sensitivity among different SSRIs has been suggested as some reports have described cutaneous eruptions experienced by the same patients to two or more of these drugs (5). It may be related to a shared mechanism of action or to a common excipient.…”
Section: Discussionmentioning
confidence: 99%
“…[10] The cross-sensitivity among them has been uncommonly reported between paroxetine and sertraline. [78] Our case is of particular interest because in the previous two reports rash was initially noted first on exposure to paroxetine followed by sertraline; however, reverse scenario has been seen in our patient who may have experienced an adverse drug reaction and possible cross-reactivity, since paroxetine was started after 10 days of sertraline discontinuation while the usual washout time for sertraline is about 7 days (The half-life of sertraline is approximately 25 h; and it has a less potently active metabolite with half life of 60 to 70 h). [12] The chronology of events suggested that both reactions were caused by the SSRIs, suggesting a class effect although the confirmative validative patch test could not be done due to patient's refusal.…”
Section: Discussionmentioning
confidence: 99%
“…A computerized MEDLINE search on the above subject yielded a report of two cases of possible cross-sensitivity between SSRIs, and in both the cases paroxetine was involved. [78]…”
Section: Introductionmentioning
confidence: 99%
“…There are a few reports of rashes developing during SSRI treatment (Charbonnier et al, 1987;Koran et al, 2003;Sannicandro et al, 2002;Spigset, 1999;Thedenat et al, 2001;Warnock and Azadian, 2002). and there are also case reports of allopecia in patients on SSRIs (Mercke et al, 2000).…”
Section: Side-effect Profilementioning
confidence: 99%